The modification of nagios web config using PHP / Norfazalizah Samsir - Samsir, Norfazalizah (2007)
Nagios Web Config is a plugins for Nagi os configuration files. It generally can run configuration files via w eb interfaces and write it to the text files. Currently, Nagios Web Config can support Nagios ve rsion 2.x and the current version of Nagios Web Config is vers ion 1.3-2. This plugins important to the network administrator because they can save time to configure Nagi os files and the web interfaces makes it program easier to understands and manag e. However, if they need to configure the Nagios configur ation files manually vi a text files, the network admin find it difficult to configure the confi guration files. It is because they need to understand the struct ure of the configuration f iles. As a result, they will waste their time to configure and m onitor network. This plugins has it own limitation that it cannot copy old configuration files before the plugins configuration and there ar e certain function missing in this plugins. The modification of Nagios Web Config by using PHP programming was designed to overcome the problem. The project uses Linux operating system , apache server, PHP application and also other related software. Data fo r config files retrieve from network monitoring system which is from Nagios will be writen to the text files and the text configur ation files will be updated. In conclusion, it is recommended that this project would be mo re beneficial to the organization that are using Nagios Network Monitoring tools as their network monitoring tools in order to check their Nagios configurati on and network condition at any time in better ways.